2019
DOI: 10.1044/2019_lshss-voia-18-0135
|View full text |Cite
|
Sign up to set email alerts
|

To See or Not to See: How Does Seeing Spellings Support Vocabulary Learning?

Abstract: Purpose The aim of this study was to determine when, why, and how the presence of a word's written form during instruction aids vocabulary learning (a process known as orthographic facilitation ). Method A systematic review of the research on orthographic facilitation was carried out. PsycInfo, Web of Science, ProQuest, and OpenGrey databases were searched. The search returned 3,529 results, and 23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…Acquisition of phonological representations is further supported by practicing grapheme-phonememappings and reading and spelling of words. The beneficial effect of print exposure on novel word learning (orthographic facilitation) described in the introduction has proved reliable in a recent systematic review of 23 studies (Colenbrander et al 2019). In alphabetic systems, orthographic word forms are well specified and systematically related to pronunciations.…”
Section: Inspection Ofmentioning
confidence: 97%
“…Acquisition of phonological representations is further supported by practicing grapheme-phonememappings and reading and spelling of words. The beneficial effect of print exposure on novel word learning (orthographic facilitation) described in the introduction has proved reliable in a recent systematic review of 23 studies (Colenbrander et al 2019). In alphabetic systems, orthographic word forms are well specified and systematically related to pronunciations.…”
Section: Inspection Ofmentioning
confidence: 97%
“…Given the evidence of TD children and adults benefitting from the presence of orthographic representations during word learning, the current study aimed to determine if there is evidence in the literature that clinical populations such as DLD or language disorder associated with other diagnoses would also benefit from the presence of orthography during word learning tasks. A recent synthesis on word learning with orthography across all populations demonstrated that there is strong evidence of an orthographic facilitation effect in the areas of phonology and spelling and weaker evidence of an orthographic facilitation effect in the area of semantics (Colenbrander et al, 2019). This synthesis emphasized the need for further research in ecologically valid environments (i.e., classrooms) to determine if orthographic facilitation can occur in large group settings.…”
Section: This Studymentioning
confidence: 99%
“…Direct instruction of targeted vocabulary items increases reading comprehension and is one instructional strategy used in classrooms (e.g., Archer & Hughes, 2010;Beck & McKeown, 2007). Showing a word's orthographic representation during learning activities has been shown to facilitate word learning for typically developing (TD) children (e.g., Ehri & Wilce, 1979;Jubenville et al, 2014;Nelson et al, 2005;O'Leary, 2017;Ricketts et al, 2009;Rosenthal & Ehri, 2008; for a review, see Colenbrander et al, 2019). This review article aims to systematically review the literature for studies that compare vocabulary learning with and without the support of orthography for children and adolescents from clinical populations, such as developmental language disorder (DLD), 1 intellectual disabilities, autism spectrum disorder (ASD), Down syndrome, hearing impairment, cerebral palsy, and dyslexia.…”
mentioning
confidence: 99%
“…An efficient reader could make use of the available reading context or available cues to enhance reading performance. For example, students may intentionally skip unfamiliar words in a reading task (Ardasheva et al, 2017;Suk, 2017;Wright and Cervetti, 2017). In this case, students may not even use any VLS to learn unfamiliar words, as a lower percentage of unfamiliar words does not present an obstacle to reading-materials comprehension.…”
Section: Vls Examinationmentioning
confidence: 99%